Ectodysplasin-A (EDA) Signaling Cross-Talk in Skeletogenesis - Ahi, Ehsan Pashay; Moustakas-Verho, Jacqueline; Singh, Pooja (Springer Nature, 2026)
Skeletal morphogenesis is a highly complicated interaction cascade of molecular cues, with the Ectodysplasin-A (EDA) pathway emerging as a potentially important contributor to this biological process. This review focuses on the molecular complexity of the EDA pathway’s role in shaping the diverse skeletal architectures observed in vertebrate models studied to date, particularly in fish and mammals. At the molecular level, we first discuss the signaling cascades initiated by EDA and briefly explore its impact on skeletal development. Insights into the transcriptional regulation and downstream effectors activated by EDA provide a greater understanding of its influence on skeletal formation. Beyond its standalone role in skeletogenesis, the review mainly focuses on the dynamic cross-talk between the EDA pathway and other important skeletogenic/morphogenic pathways. The multi-layered interplay with signaling networks, such as BMP, Hedgehog, Wnt, and FGF, highlights the integration of this pathway into broader molecular process governing skeletal morphogenesis. The physiological role of EDA in skeletal tissues appears highly context-dependent, varying with the interacting pathway, cell type, and developmental stage. We explore instances where EDA acts as a conductor, harmonizing its effects with those of other pathways to achieve distinct outcomes in skeletal diversity, and propose a conceptual framework in which EDA integrates these inputs through shared transcriptional hubs, notably NF-κB and NFATc1, in a tissue- and stage-specific manner. By summarizing the interactions of EDA and their associated physiological roles, we provide a comprehensive perspective on the EDA-dependent molecular underpinnings of skeletal diversity, offering new and valuable insights for future research and potential applications in skeletal biology.